Extensive Remineralization of Large Pelvic Lytic Lesions Following Total Therapy Treatment in Patients With Multiple Myeloma. (27th March 2017) - Mohan, Meera; Samant, Rohan S; Yoon, Donghoon; Buros, Amy F; Branca, Antonio; Montgomery, Corey O; Nicholas, Richard; Suva, Larry J; Morello, Roy; Thanendrarajan, Sharmilan; Schinke, Carolina; Yaccoby, Shmuel; et al.
ABSTRACT: Osteolytic bone lesions are a hallmark of multiple myeloma (MM) bone disease. Bone destruction is associated with severely imbalanced bone remodeling, secondary to increased osteoclastogenesis and significant osteoblast suppression. Lytic lesions of the pelvis are relatively common in MM patients and are known to contribute to the increased morbidity because of the high risk of fracture, which frequently demands extensive surgical intervention. After observing unexpected radiological improvement in serial large pelvic CT assessment in a patient treated in a total therapy protocol, the radiographic changes of pelvic osteolytic lesions by PET/CT scanning in patients who received Total Therapy 4 (TT4) treatment for myeloma were retrospectively analyzed. Sixty‐two (62) patients with lytic pelvic lesions >1 cm in diameter were identified at baseline PET/CT scanning. Follow‐up CT studies showed that 27 of 62 patients (43%) with large baseline pelvic lesions achieved significant reaccumulation of radiodense mineralization at the lytic cortical site. The average size of lytic lesions in which remineralization occurred was 4 cm (range, 1.3 to 10 cm). This study clearly demonstrates that mineral deposition in large pelvic lesions occurs in a significant proportion of MM patients treated with TT4, potentially affecting patient outcomes, quality of life, and future treatment strategies. © 2017 American Society for Bone and Mineral Research.